(untitled) (Journal of Applied Oral Science, 2016)
To improve orthodontic treatment efficiency, orthodontists must know which variables could interfere with orthodontic treatment time. Objective: To identify variables and their effect size on orthodontic treatment time of Class III malocclusion. Material and Methods: Forty-five Class III malocclusion cases were selected from 2008 patients’ records. Clinical charts, cephalometric radiographs, and pre and posttreatment dental casts were evaluated. Age, sex, PAR index at T1 and T2, overjet, missing teeth, extractions, number of treatment phases, missed appointments, appliance breakages, and cephalometric variables SNA, SNB, ANB, Wits, SnGoGn, CoA, CoGn, IMPA, 1.PP were investigated by multiple linear regression analysis and stepwise method at p;2 (patients who missed more than 2 appointments), to detect the influence of this data on treatment time and the quality of the treatment (PAR T2). Results: Average treatment time was 30.27 months. Multiple regression analysis showed that missed appointment (R2=0.4345) and appliance breakages (R2=0.0596) are the only variables able to significantly predict treatment duration. Treatment time for patients who missed more than 2 appointments was nearly one year longer. However, no significant influence on PAR T2 was observed for those patients. Conclusion: Orthodontic treatment duration in Class III patients is mainly influenced by factors related to patient compliance. Patients who missed more appointments did not show worse orthodontic finishing, but longer treatment. No occlusal, cephalometric, or demographic variable obtained before treatment was able to give some significant prediction about treatment time in Class III patients.